Intra-subunit residue interactions from the protein surface to the active site of glutathione S-transferase AdGSTD3-3 impact on structure and enzyme properties - Jeerang Wongtrakul (2018)
Structural residues are one of the major factors that modulate the catalytic specificity as well as having a role in stability of the glutathione S-transferases (GST). To understand how residues remote from the active site can affect enzymatic properties, four mutants, His144Ala, Val147Leu, Val147Ala and Arg96Ala, were generated. The selected residues appear to be in a putative intra-subunit interaction pathway from the exterior Asp150 to the active site Arg66 of AdGSTD3-3. The analysis of the four mutants suggested that the interaction formed between Asp150 and His144 is required for the packing of the hydrophobic core in domain 2. Mutations of both Asp150 and His144 impacted upon enzymatic properties. Two Val147 mutants also showed contribution to packing and support of the N-capping box motif by demonstrating shorter half-lives. The planar guanidinium of Arg96 is in a stacked geometry with the face of the aromatic ring of Phe140 in a cation-π interaction. The Arg96 also interacts with several other residues one of which, Asp100, is in the active site. These interactions restrict movement of the residues in this region and as the data demonstrates when Arg96 is changed have dramatic impact on stability and enzyme properties. These findings indicate the significance of the roles played by residue interactions which can cause conformational changes and thereby influence the catalytic activity and stability of an enzyme. © 2004 Elsevier Ltd. All rights reserved.